2022
DOI: 10.1080/21645515.2022.2115751
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of influenza vaccine among elderly Chinese: A regression discontinuity design based on Yinzhou regional health information platform

Abstract: In China, a free influenza vaccination policy is being implemented among individuals aged 70 years and over in Zhejiang province during the COVID-19 pandemic. The objective was to assess the effectiveness of influenza vaccine in reducing hospitalization and mortality in the elderly. We used data from the Regional Health Information Platform in Yinzhou located in Zhejiang province and applied a regression discontinuity design to estimate the intention-to-treat effect on admission and mortality rates by month of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Other large‐scale studies include a diabetes study, 48 a herpes zoster incidence study conducted to generate baseline data in view of the introduction of the zoster vaccine in China, 51 and rheumatoid arthritis epidemiology 57 . Other studies have evaluated childhood and adult vaccine administration and safety (including HPV vaccines) 45,52–56,58–60 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other large‐scale studies include a diabetes study, 48 a herpes zoster incidence study conducted to generate baseline data in view of the introduction of the zoster vaccine in China, 51 and rheumatoid arthritis epidemiology 57 . Other studies have evaluated childhood and adult vaccine administration and safety (including HPV vaccines) 45,52–56,58–60 …”
Section: Resultsmentioning
confidence: 99%
“…57 Other studies have evaluated childhood and adult vaccine administration and safety (including HPV vaccines). 45,[52][53][54][55][56][58][59][60] Findings from a 2018 survey of electronic data sources suitable for vaccine research in the Asia-Pacific region indicated that the YRHIP offers relevant vaccine-specific outcome data. 44 A presentation at the ACPE on the value of the YRHIP to generate safety outcome data for a range of recommended infant vaccines, 61 with more complete data subsequently published, further informed our feasibility assesment.…”
Section: Disease Area Reference Study Period Key Observationsmentioning
confidence: 99%
“…Consequently, we applied the RDD using birth month as the running variable with a cutoff of March 1957. Several studies have estimated the causal relationships between influenza, COVID-19 vaccinations, and health outcomes using RDD with age or birth timing as the running variables [ 18 21 ]. However, to the best of our knowledge, few studies have investigated the causal relationship between COVID-19 vaccination and protective behaviors against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The autoregressive integrated moving average (ARIMA) models, accommodating alterations in trends, variations in periodicity, and random disturbances within a time series, have seen extensive application in predicting infectious diseases (3)(4)(5). Our study aimed to depict the temporal patterns of varicella outbreak cases in China spanning 2005-2018, assess the practicality of employing ARIMA models to project upcoming monthly varicella outbreak cases, and contribute empirical evidence for early alarms and effective prevention measures to suppress varicella outbreaks.…”
mentioning
confidence: 99%